Mechanisms of Cardiovascular System Injury Induced by COVID-19 in Elderly Patients With Cardiovascular History - Yang, Yaliu; Yan, Mengwen (Frontiers in Cardiovascular Medicine, 2022)
The coronavirus disease-2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus (SARS-CoV-2), represents a great threat to healthcare and socioeconomics worldwide. In addition to respiratory manifestations, COVID-19 promotes cardiac injuries, particularly in elderly patients with cardiovascular history, leading to a higher risk of progression to critical conditions. The SARS-CoV-2 infection is initiated as virus binding to angiotensin-converting enzyme 2 (ACE2), which is highly expressed in the heart, resulting in direct infection and dysregulation of the renin-angiotensin system (RAS). Meanwhile, immune response and hyper-inflammation, as well as endothelial dysfunction and thrombosis implicate in COVID-19 infection. Herein, we provide an overview of the proposed mechanisms of cardiovascular injuries in COVID-19, particularly in elderly patients with pre-existing cardiovascular diseases, aiming to set appropriate management and improve their clinical outcomes.